Role of CT-PNS in non-neoplastic sino-nasal diseases: an observational study at tertiary care center in South Gujarat - Patel, Rahul B.; Nair, Nidhi R.; Contractor, Jaymin A.; Patel, Jalpadevi A.; Vasani, Ankita M. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Role of CT scan in sinonasal disease is proved by many published articles. Most of them are having small sample size, poorly defined protocol of CT reporting and does not mention the window width and window level of the software. We did this study to include these points and tried to have sample size of at least 200. Methods: 231 patients included in the study. After clinical examination CT PNS was done. A strict protocol was maintained for the timing of CT, window settings (to get highest bony definition) and for the reporting of CT. Results: Few common anatomical variations were agger nasi (61.9%), DNS in 50.6%; concha bullosa (18.6%), paradoxical MT (20.3%), Onodi Cells (21.6%) and Haller cells (11.3%). Most common subtypes amongst some anatomical variations include middle meatal drainage of frontal recess (58.8%), type I frontal cell (7.1%), type I ethmoid roof (48.9%), type I attachment of UP (58.8%) and sellar type of sphenoid pneumatization (68%). CT has 100% sensitivity and specificity in detecting the diseased sinuses correctly. Except from 11.8% cases in which frontal recess drainage could not be assessed, all other anatomical variation were same intra-op as shown by CT. In fungal rhinosinusitis anatomical variations were difficult to detect by CT. Conclusions: This study proves that CT-PNS gives us the detailed and near exact picture of the disease with its extent as well as of existing anatomical variations in non-neoplastic sino-nasal diseases except in FRS cases where in anatomical variations are difficult to analyze.